DO NSAIDS CAUSE SPECIFIC COMPLICATIONS IN COVID-19 CORONAVIRUS INFECTION? - A. E. Karateev; E. L. Nasonov; A. M. Lila (Научно-практическая ревматология)
Currently, there is no clear data indicating the risk of specific complications when using non-steroidal anti-inflammatory drugs (NSAIDs), and in particular ibuprofen, for COVID-19 infection. There is also no clear clinical evidence that taking NSAIDs increases the risk of COVID-19 infection. However, when using NSAIDs in patients with acute respiratory viral diseases, keep in mind the possibility of class-specific complications from the gastrointestinal tract, cardiovascular system and kidneys. This risk is quite serious in elderly patients with multiple comorbid diseases. In addition, you should remember that taking NSAIDs and paracetamol can mask important symptoms of COVID-19 infection (in particular, fever) and lengthen the time for making a correct diagnosis.